Identification of MLH2/hPMS1 dominant mutations that prevent DNA mismatch repair function - Reyes, Gloria X.; Zhao, Boyu; Schmidt, Tobias Thomas; Gries, Kerstin; Kloor, Matthias; Hombauer, Hans (Communications biology, 2020)
Inactivating mutations affecting key mismatch repair (MMR) components lead to microsatellite instability (MSI) and cancer. However, a number of patients with MSI-tumors do not present alterations in classical MMR genes. Here we discovered that specific missense mutations in the MutL homolog MLH2, which is dispensable for MMR, confer a dominant mutator phenotype in S. cerevisiae. MLH2 mutations elevated frameshift mutation rates, and caused accumulation of long-lasting nuclear MMR foci. Both aspects of this phenotype were suppressed by mutations predicted to prevent the binding of Mlh2 to DNA. Genetic analysis revealed that mlh2 dominant mutations interfere with both Exonuclease 1 (Exo1)-dependent and Exo1-independent MMR. Lastly, we demonstrate that a homolog mutation in human hPMS1 results in a dominant mutator phenotype. Our data support a model in which yeast Mlh1-Mlh2 or hMLH1-hPMS1 mutant complexes act as roadblocks on DNA preventing MMR, unraveling a novel mechanism that can account for MSI in human cancer.
Gesehen am 12.02.2021